2021
DOI: 10.1049/tje2.12033
|View full text |Cite
|
Sign up to set email alerts
|

WG 2 AN: Synthetic wound image generation using generative adversarial network

Abstract: In part due to its ability to mimic any data distribution, Generative Adversarial Network (GAN) algorithms have been successfully applied to many applications, such as data augmentation, text-to-image translation, image-to-image translation, and image inpainting. Learning from data without crafting loss functions for each application provides broader applicability of the GAN algorithm. Medical image synthesis is also another field that the GAN algorithm has great potential to assist clinician training. This pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…The ROC curve and the AUC provide a visualization related to the performance of the model on the classification task. The performance of the model could be improved with a larger training dataset [45] and fine-tuning the hyperparameters [46].…”
Section: Resultsmentioning
confidence: 99%
“…The ROC curve and the AUC provide a visualization related to the performance of the model on the classification task. The performance of the model could be improved with a larger training dataset [45] and fine-tuning the hyperparameters [46].…”
Section: Resultsmentioning
confidence: 99%
“…Training the model with less than 400 epochs leads to an abundant amount of noise in the simulated SSI maps. When the epoch number is increased from 600 to 1,000, it potentially results in a decline in In most of the studies, GANs need a large epoch number (>100) to reach the best performance (Bird et al, 2022;Robic-Butez & Win, 2019;Sarp, Kuzlu, Pipattanasomporn, & Guler, 2021;Sarp, Kuzlu, Wilson, & Guler, 2021); while there are a few studies that reported lower epoch numbers to train their proposed GAN or use an already existing GAN for an application (Laloy et al, 2018;Li et al, 2020). Generally, there is no universal agreement on the optimal epoch number for training a GAN network.…”
Section: Determining the Optimum Epoch Numbermentioning
confidence: 99%
“…Early non-parametric image style transfer is a method of then analyzing style images, drawing a physical model or a mathematical statistical model according to the style, and then synthesizing the texture of the transferred image to make it more in line with the established model [1,2,3]. This method requires the establishment of complex models, which has high theoretical requirements, and each style needs to be modeled separately, which is time-consuming and laborintensive [4,5,6].…”
Section: Introductionmentioning
confidence: 99%